2013
DOI: 10.1590/s1808-18512013000300003
|View full text |Cite
|
Sign up to set email alerts
|

Canal lombar estreito: sinal da sedimentação

Abstract: Objective: To verify the presence of the sedimentation sign in patients with lumbar spinal stenosis (LSS) in comparison to those without LSS. Methods: Retrospective, cross-sectional and descriptive study. Review of the imaging processes of patients with LSS operated between January 1, 2008 and December 31, 2009, comparing with patients without LSS observed in outpatient consultations. Patients were divided into two groups: group I had 34 patients with a diagnosis of LSS. Diagnostic criteria: existence of low b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…With the increased life expectancy of the population due to lifestyle changes and the practice of healthy activities, degenerative conditions of several joints and of the lumbar spine play a much greater role in the day-to-day routine of spine surgeons. [1][2][3] Several tools for the better diagnosis, classification, and treatment of these illnesses are described in the literature. 6,7,[10][11][12] In patients with lumbar stenosis, magnetic resonance can show the degree of narrowing, the characteristics of structures, such as the disc and the ligamentum flavum, and the disposition of the nerve roots at high quality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…With the increased life expectancy of the population due to lifestyle changes and the practice of healthy activities, degenerative conditions of several joints and of the lumbar spine play a much greater role in the day-to-day routine of spine surgeons. [1][2][3] Several tools for the better diagnosis, classification, and treatment of these illnesses are described in the literature. 6,7,[10][11][12] In patients with lumbar stenosis, magnetic resonance can show the degree of narrowing, the characteristics of structures, such as the disc and the ligamentum flavum, and the disposition of the nerve roots at high quality.…”
Section: Discussionmentioning
confidence: 99%
“…The criterion used for the subdivision was the nerve root sedimentation sign, which is present in A1 and A2 (being designated A-1) and absent in A3 and A4 (being designated A-2). 3 After the questionnaires were applied and the respective scores calculated, the data used were the percentage of dysfunction as determined by the ODI, the physical (PCS) and mental (MCS) function scores and symptom severity scales (painful and neuroischemic) found in the SF-36, the physical function scale as measured by the SSS, in addition to the scores from the EQ-5D questionnaire. Patient satisfaction, which is a part of the SS, was not used because none of the patients had yet been submitted to surgical treatment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Barz et al 3 demonstrated that patients without vertebral stenosis submitted to magnetic resonance imaging (MRI) presented a migration of the roots to the dorsal region of the dural sac due to gravitational action, whereas in patients with vertebral stenosis they found images of the roots without this conformation, thus defining the first as a sign of sedimentation present and the second as a sign of absent sedimentation ( Figure 1). 4,5 Patients with lumbar stenosis present variable clinical manifestations such as neurogenic claudication that manifests as a sensation of weight in the lower back radiating to the buttocks and lower limbs, numbness, weakness or burning; and sciatica as the most common complaints. Usually the symptoms do not accompany dermatomes, they are related to the physical activity and the patient adopts posture in flexion of the spine when wandering to decrease the complaints.…”
Section: Introductionmentioning
confidence: 99%